Antimicrobial and biological effects of BOMPHOS and PHOMPHOS on bacterial and yeast cells - Konar, V; Yilmaz, Ö; Öztürk, A; Kirbag, S; Arslan, M (Academic Press Inc, 2000)
In this study, the antimicrobial effects of monophosphazenes such as SM, BOMPHOS, and PHOMPHOS were examined on bacterial and yeast strains. In addition, the biological effects of these compounds were tested on the Saccharomyces cerevisiae and Candida albicans cells. The SM has an antimicrobial effect on the bacterial and yeast strains within the range of 100 and 1500 mug. When the concentration was increased, the inhibition zone expanded on the growth media (P < 0.01; P < 0.001). Like SM, BOMPHOS molecule has antimicrobial activity on the bacterial and yeast cells. The most effective concentrations of BOMPHOS on the microoganisms were observed by 1500 mug (P < 0.001). The PHOMPHOS did not effect on the bacterial and yeast cells between 100 and 1000 range, but it has an antimicrobial effect in 1500 g. In vitro media, the biological effects of these molecules were compared with vitamin E, melatonin, and fish oil on the yeast cells. In S. cerevisiae growth media, the cell densities were increased SM, BOMPHOS, and PHOMPHOS after 20, 30, and 45 h, The highest increase in the cell density were observed in media of BOMPHOS. In C. albicans growth media, the cell density was increased by melatonin after 20, 30, and 45 h, but were decreased by other supplemental groups. Lipid level of S. cerevisiae was reduced by administered 300 and 1000 pg vitamin E and fish oil (P < 0.01). In addition, the lipid level of the same yeast cell were diminished by the 1000 g melatonin and 300 mug PHOMPHOS (P < 0.05, P < 0.01). The lipid level of C. albicans were increased by vitamin E and BOMPHOS and fish oil, but was decreased with PHOMPHOS (P < 0.01). In conclusion, while high concentration of PHOMPHOS has antimicrobial effects on the bacterial and yeast cells, the SM and BOMPHOS have antimicrobial effects in all the concentrations. PHOMPHOS decreased the lipid lever of C. albicans, but BOMPHOS increased in the the same yeast cell. In addition, the antioxidants such as vitamin E, melatonin, and fish oils have affected on the lipid synthesis of yeast cells. (C) 2000 Academic Press.
Keywords: monophosphazenes; antimicrobial and biological effects; vitamin E; melatonin; fish oil; bacterial and yeast cells